2017
DOI: 10.1523/jneurosci.2826-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid Precursor Protein inDrosophilaGlia Regulates Sleep and Genes Involved in Glutamate Recycling

Abstract: Amyloid precursor protein (App) plays a crucial role in Alzheimer's disease via the production and deposition of toxic β-amyloid peptides. App is heavily expressed in neurons, the focus of the vast majority of studies investigating its function. Meanwhile, almost nothing is known about App's function in glia, where it is also expressed, and can potentially participate in the regulation of neuronal physiology. In this report, we investigated whether , the homolog of , could influence sleep-wake regulation when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 65 publications
1
43
0
Order By: Relevance
“…A direct connection between cortex glial cells and astrocyte‐like glial cells was also demonstrated following inhibition of the Drosophila Amyloid precursor protein homolog Appl in cortex glial cells. This resulted in higher sleep amounts correlating with changes in expression in glutamine synthetase (GS) in astrocyte‐like glia and in changes in the gap‐junction component Innexin2 in cortex glia (Farca Luna, Perier, & Seugnet, ).…”
Section: Cortex Glial Cellsmentioning
confidence: 99%
“…A direct connection between cortex glial cells and astrocyte‐like glial cells was also demonstrated following inhibition of the Drosophila Amyloid precursor protein homolog Appl in cortex glial cells. This resulted in higher sleep amounts correlating with changes in expression in glutamine synthetase (GS) in astrocyte‐like glia and in changes in the gap‐junction component Innexin2 in cortex glia (Farca Luna, Perier, & Seugnet, ).…”
Section: Cortex Glial Cellsmentioning
confidence: 99%
“…Similar to mammalian glia, Drosophila glia include multiple specialized cell types (Kremer, Jung, Batelli, Rubin, & Gaul, ) and are essential for neuronal development (Booth, Kinrade, & Hidalgo, ; Sepp, Schulte, & Auld, ) and maintenance (Xiong & Montell, ). In the adult nervous system, they serve many of the same specialized functions as mammalian glia, including phagocytic clearance of cellular debris (Doherty, Logan, Taşdemir, & Freeman, ; MacDonald et al, ), participation in innate immunity (Kounatidis & Chtarbanova, ), blood–brain barrier formation (DeSalvo et al, ), glutamate recycling (Farca Luna, Perier, & Seugnet, ; Rival et al, ), protection of axons in white matter (Logan et al, ), and protection of neurons from reactive oxygen species through lipid droplet formation (L. Liu, MacKenzie, Putluri, Maletić‐Savatić, & Bellen, ; L. Liu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple glial subtypes have been identified that regulate sleep in Drosophila [13]. Moreover, glial dysfunction is associated with aging, and numerous models of neurodegeneration in flies [711]. Despite these bidirectional interactions between glia and sleep, surprisingly little is known about the mechanisms through which sleep-deprivation impacts glial function, and how this contributes to neurodegenerative disease.…”
Section: Resultsmentioning
confidence: 99%